(untitled) (Medico Legal Update, 2020)
In recent decades, there has been an increase in the use of composite graft in the closure of the tympanic membrane perforation. The aim of this research is to know the change of tympanogram and audiogram presentation after tympanomastoidectomy surgery using musculus temporalis fascia profunda graft and composite graft. Experimental research was being conducted on 22 Otitis Media Suppurative Chronic patients without cholesteatoma such as 14 patients using musculus temporalis fascia profunda graft and 8 patients using composite graft. The Audiometric tests were being administered twice, before and after tympanomastoidectomy surgery, in other hand tympanometry test was being performed after surgery. Data analysis using independent-t test, paire-t test, and chi square test. The research has shown that the Pure Tone Audiometry post-surgeries were being found higher on composite graft (68,4) in comparison with musculus temporalis fascia profunda graft (55,1), but statistically non-significant (p>0,05). On the contrary, on fascia graft group was being found significantly higher 1,47 than amplitudo composite graft (0,87), statistically significant (p<0,001). Clinical meaning of using musculus temporalis fascia profunda graft is better than composite graft in terms of hearing and tympanic membrane elasticity.